Candidate and supervisor experiences of doctoral study in a structured, interdisciplinary training environment - Kiley, Margaret; Halliday, Douglas P. (Innovations in Education and Teaching International, 2025)
This study aimed to understand doctoral candidates’ and supervisors’ positive and negative experiences of undertaking a doctorate in a structured interdisciplinary research training environment. Interviews were held with 16 candidates and eight supervisors involved in an interdisciplinary research centre. Most candidates were undertaking a disciplinary focussed doctorate while being active participants in the centre’s doctoral education program. Our findings highlighted three themes that influence positive or negative experiences: the design of the interdisciplinary environment; the critical role of communication; and the qualities of candidates and supervisors deemed important to work effectively in such an environment. We conclude with suggestions that might help develop an effective interdisciplinary research environment.
EPrint Processing Status: Full text deposited in DRO